Hak Prerogatif Presiden Dalam Pengangkatan Menteri - Jacoba F X Kelbulan; Saartje Sarah Alfons; Hendry John Piris (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The use of prerogatives in appointing ministers, the president must pay attention to the educational background of a minister, the president must also look at some applicable standards.Purposes of the Research: to know and understand how to regulate the use of the President's prerogative in the appointment of ministers and how to use the mechanism of the President's prerogative in the appointment of ministers. Methods of the Research: In this legal research, the author uses normative research. Normative research is library research, where in normative research library materials are data sources which are classified as secondary data in research. Secondary data has a broad scope, ranging from personal letters, book, to afficial documents issued by the government.Results of the Research: Regarding the educational background of the minister, Susie pudjiastuti, it is not regulated because the ministerial position is not a structural position. Although the president has prerogatives, the president is not necessarily given the widest freedom in appointing a minister. Special arrangements need to be made to limit the president regarding certain things that are the measure. The mechanism of the president's prerogative regarding the appointment of ministers needs to be regulated in a statutory regulation. The intended mechanism can be in the form of interviews, as well as fit and proper tests from the minister concerned, and the conditions that allow it to be open to the public.